Back Cover: Laser stimulating ST36 with optical fiber induce blood component changes in mice: a Raman spectroscopy study (J. Biophotonics 6/2018). Issue 6 (8th June 2018) - Zhang, Heng; Chen, Zhenyi; Wu, Jiping; Chen, Na; Xu, Wenjie; Li, Taihao; Liu, Shupeng
Abstract : Optical fiber laser acupuncture with combination of traditional needling acupuncture and the laser stimulation makes stronger therapeutic effects in this study, showing a potential value in clinical application. In mice model, Raman spectroscopic technique is used to analysis the changes of blood components after stimulating on ST36 with it and shows spectral changes. This study explores the optical fiber acupuncture's effect using Raman spectroscopy technique for mechanism of acupuncture therapy. Further details can be found in the article by Heng Zhang et al. (e201700262 ). Abstract : Optical fiber laser acupuncture with combination of traditional needling acupuncture and the laser stimulation makes stronger therapeutic effects in this study, showing a potential value in clinical application. In mice model, Raman spectroscopic technique is used to analysis the changes of blood components after stimulating on ST36 with it and shows spectral changes. This study explores the optical fiber acupuncture's effect using Raman spectroscopy technique for mechanism of acupuncture therapy. Further details can be found in the article by Heng Zhang et al. (e201700262 ).